PELATIHAN KETERAMPILAN DAN PENGETAHUAN HANDUK LEMBAB (OSHIBORI) - Lapotulo, Nensi; Sukmamedian, Haufi; Mulyadi, Mulyadi (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
Moist towel (osihibori) skills and knowledge training aims to increase knowledge and skills in making and managing it. Oshibori is wet towel used to clean hands in hotels, restaurants and other public places. This training was carried out with the aim of improving service quality and guest satisfaction. Skills and knowledge training consists of understanding, folding techniques and presentation techniques. Training is carried out using lecture, demonstration and direct practice methods. The results show that participants can improve their knowledge and skills in managing oshibori well.